Paradigm lost, or is top-down forcing no longer significant in the Antarctic marine ecosystem? - Ainley, D.; Ballard, G.; Ackley, S.; Blight, L. K.; Eastman, J. T.; Emslie, S. D.; Lescroel, A.; Olmastroni, S.; Townsend, S. E.; Tynan, C. T.; Wilson, P.; Woehler, E. (Antarctic Science, 2007)
Investigations in recent years of the ecological structure and processes of the Southern Ocean have almost exclusively taken a bottom-up, forcing-by-physical-processes approach relating various species' population trends to climate change. Just 20 years ago, however, researchers focused on a broader set of hypotheses, in part formed around a paradigm positing interspecific interactions as central to structuring the ecosystem (forcing by biotic processes, top-down), and particularly on a "krill surplus" caused by the removal from the system of more than a million baleen whales. Since then, this latter idea has disappeared from favour with little debate. Moreover, it recently has been shown that concurrent with whaling there was a massive depletion of finfish in the Southern Ocean, a finding also ignored in deference to climate-related explanations of ecosystem change. We present two examples from the literature, one involving gelatinous organisms and the other involving penguins, in which climate has been used to explain species' population trends but which could better be explained by including species interactions in the modelling. We conclude by questioning the almost complete shift in paradigms that has occurred and discuss whether it is leading Southern Ocean marine ecological science in an instructive direction. © 2007 Antarctic Science Ltd.